Likuiditas, Return On Assets, Leverage Dan Ukuran Perusahaan Terhadap Agresivitas Pajak - Eni Endaryati; Vivi Kumalasari Subroto; Sri Wahyuning (Universitas Sains dan Teknologi Komputer, 2021)
Tax aggressiveness is the actions taken by the company to reduce its tax obligations. A company is said to carry out tax aggressiveness if the company tries to reduce the tax burden aggressively, either using legal methods, namely tax avoidance or illegal methods such as tax evasion. Although not all tax planning actions are carried out illegally, the more loopholes a company uses to avoid taxes, the more aggressive the company is considered. And this study aims to examine the relationship between the dependent variable and the independent variable of this study. The independent variables are liquidity, ROA, leverage and firm size and the dependent variable is tax aggressiveness. And for the analytical method used is regression analysis, and descriptive analysis. Descriptive statistics are used to describe or describe the variables in the study. Descriptive statistics used are measures of tax aggressiveness of all sample companies. The description of the variables can be seen from the mean and standard deviation. The descriptive statistical test was carried out with the SPSS program. The results of the study found that liquidity has no effect on tax aggressiveness, then Renturn on Assets (ROA) affects tax aggressiveness, then leverage affects tax aggressiveness and company size affects tax aggressiveness. Keywords: Liquidity, ROA, Leverage, Company Size, Tax Aggressiveness